2015
DOI: 10.1186/s12982-015-0035-6
|View full text |Cite
|
Sign up to set email alerts
|

Development of an international scale of socio-economic position based on household assets

Abstract: BackgroundThe importance of studying associations between socio-economic position and health has often been highlighted. Previous studies have linked the prevalence and severity of lung disease with national wealth and with socio-economic position within some countries but there has been no systematic evaluation of the association between lung function and poverty at the individual level on a global scale. The BOLD study has collected data on lung function for individuals in a wide range of countries, however … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 21 publications
0
18
0
3
Order By: Relevance
“…We therefore referred to these scores as "wealth scores", as they are broadly indicative of an individual's wealth. We previously showed that the rank ordering of prevalence of ownership of these assets was fairly consistent across a wide range of countries with GNI/capita ranging from $4750 to $53 760 (Cronbach's alpha=0.96), suggesting that this is a useful scale to compare individuals both within and between countries [12].…”
Section: Methodsmentioning
confidence: 88%
See 3 more Smart Citations
“…We therefore referred to these scores as "wealth scores", as they are broadly indicative of an individual's wealth. We previously showed that the rank ordering of prevalence of ownership of these assets was fairly consistent across a wide range of countries with GNI/capita ranging from $4750 to $53 760 (Cronbach's alpha=0.96), suggesting that this is a useful scale to compare individuals both within and between countries [12].…”
Section: Methodsmentioning
confidence: 88%
“…# : individual responses have been weighted according to the probability of selection to provide population estimates of means and percentages for each of the study areas; ¶ : individuals selected for possible inclusion in the Burden of Obstructive Lung Disease (BOLD) study using a random sampling process; + : individuals included in the study (i.e. those who agreed to take part in the BOLD study and provided useable data from both the questionnaire and spirometry tests); § : 1 pack-year equals an average of 20 cigarettes per day for 1 year or the equivalent amount of other types of tobacco smoking; ƒ : somebody else in the household smoked during the past 2 weeks; ## : the respondent was employed in a dusty job for at least 1 year; ¶ ¶ : ever diagnosed with tuberculosis; ++ : a close sibling or parent had been diagnosed as having emphysema, chronic bronchitis or COPD by a health professional; § § : hospitalised for breathing problems before the age of 10 years; ƒƒ : highest level of education completed was above primary school; ### : calculated from ownership of a range of assets (see methods and [12]); ¶ ¶ ¶ : exposure to open fires for cooking and/or heating for more than 20 years; +++ : current or ex-smoker. the present analysis, as the questions on household assets were only introduced into the BOLD protocol at a relatively late stage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An alternative approach to poverty which is frequently used in health studies is the assessment of socioeconomic status (SES), a composite measure of a person's economic and social position generally based on income, occupation, education level, and home and neighbourhood conditions and environment [9]. Although some authors have questioned the assets-based methods [10], the wealth score used in Townend's study has shown close correlation with the education level and gross national income per capita of the country [11].…”
mentioning
confidence: 99%